Mutations in bla(KPC-3) That Confer Ceftazidime-Avibactam Resistance Encode Novel KPC-3 Variants That Function as Extended-Spectrum β-Lactamases - Haidar, Ghady (Antimicrob Agents Chemother, 2017)
We identified four bla(KPC-3) mutations in ceftazidime-avibactam-resistant clinical Klebsiella pneumoniae isolates, corresponding to D179Y, T243M, D179Y/T243M, and EL165-166 KPC-3 variants. Using site-directed mutagenesis and transforming vectors into Escherichia coli, we conclusively demonstrated that mutant bla(KPC-3) encoded enzymes that functioned as extended-spectrum β-lactamases; mutations directly conferred higher MICs of ceftazidime-avibactam and decreased the MICs of carbapenems and other β-lactams. Impact was strongest for the D179Y mutant, highlighting the importance of the KPC Ω-loop.